2023
DOI: 10.3390/min13091128
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Removal of Iron Impurities from Quartz Mineral

Chunfu Liu,
Weitao Wang,
Han Wang
et al.

Abstract: Iron is one of the most stubborn impurities in quartz minerals, and the iron content partly determines the various applications of quartz. Iron can exist in quartz in the forms of iron minerals, fluid inclusions, and lattice impurities. The removal of iron and the consequent purification of quartz minerals are the key processes to obtaining high-quality quartz. Iron removal methods including conventional pre-treatment, magnetic separation, acid leaching, microbiological, roasting, and flotation, as well as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Acid leaching emerges as a formidable method for addressing impurities such as iron, aluminum, and inclusions [75,76]. It is frequently harnessed to expunge thin-film iron from quartz particle surfaces and iron impurities nestled within quartz particles, in addition to other deleterious impurities [77].…”
Section: Acid Leaching Processmentioning
confidence: 99%
“…Acid leaching emerges as a formidable method for addressing impurities such as iron, aluminum, and inclusions [75,76]. It is frequently harnessed to expunge thin-film iron from quartz particle surfaces and iron impurities nestled within quartz particles, in addition to other deleterious impurities [77].…”
Section: Acid Leaching Processmentioning
confidence: 99%
“…Normally, quartz and gangue minerals (such as mica, feldspar, limonite, hematite, etc.) can be easily separated via a flotation process [3][4][5], while the impure elements in quartz lattices are the most difficult to remove [6]. Previous studies indicated that there are two kinds of lattice impurities [7][8][9][10], i.e., lattice substitution impurities, such as Si 4+ substituted by Al 3+ , Ga 3+ , Fe 3+ , B 3+ , Ge 4+ , Ti 4+ and P 5+ , in which Al 3+ is the most common ion due to its abundant reserves in Earth's crust and similar ionic radius to Si 4+ (0.54 Å vs. 0.40 Å) [11].…”
Section: Introductionmentioning
confidence: 99%